Improved bio-oil yield from thermo-catalytic pyrolysis of Citrus limetta waste over pumice: determination of kinetic parameters using Kissinger method - Muhammad, Faisal; Nisar, Jan; Ali, Ghulam; Anwar, Farooq; Hussain, Syed Tasleem; Khan, Sher Wali (Elsevier, 2023)
The focus of this research is on thermo-catalytic conversion of Citrus limetta waste, with and without pumice, using thermo gravimetric analysis and a pyrolysis chamber. TG/DTG results demonstrated weight reduction occurring in four stages i.e., evaporation of water, degradation of hemicellulose, decomposition of cellulose and lignin. Activation energy (Ea) calculated using Kissinger method for non-catalytic decomposition of hemicellulose, cellulose, and lignin was found as 99.76, 157.96 and 174.59 kJ mol−1 and for catalyzed reactions as 83.14, 91.45 and 149.65 kJ mol−1respectively. Thermal degradation of Citrus limetta waste produced 30 oil in the range of C2–C24, while catalytic pyrolysis produced more than 45 pyrolysis oil with a wide range of components from C4 to C32 which shows, that pumice has not only decreased the activation energy of the pyrolysis reaction but improved the quality of bio-oil making it suitable for energy on upgradation.